Zdrowa rodzina adopcyjna – to znaczy jaka? - Posłuszna-Owczarz, Maria (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
On the one hand, adoptive family is an alternative for married couples who are not able to have progeny, on the other hand, it is an alternative for social orphans to have proper family. So as well as fulfilling a lot of functions of biological families, adoptive families also compensate for social orphanhood. Only a healthy family can face such a responsible task. According to modern psychology, pedagogics and sociology, family is a small social group, a community which follows certain rules. A healthy family is a functional family, which makes every one of its members happy and gives them possibility to fulfill their needs. There are all sorts of difficulties, failures and arguments in such a family, however, mutual relationships and the potential of its particular members motivates to look for satisfying solutions for every one of them. So, what should characterize a healthy adoptive family, what inner-family factors and outer conditions might disturb its functioning. These questions need to be tried and answered already in the diagnosing and preparation period for the adoptive parents candidates. It is also important to prepare a child (depending on age), because both the child and its future parents bring to the newly created adoptive family their genetic heritage, health condition, previous experiences and life plans, hopes, value, skills, mutual relations, ways to communicate and deal with difficulties and so on. Final court decision on adoption should not be the end, but the beginning of post-adoptive work with the new family, in order to strengthen its proper and healthy functioning.